Breakfast Skipping, Anxiety, Exercise, and Soda Consumption are Associated with Diet Quality in Mexican College Students. Issue 3 (4th May 2017) - Hall, Laura; Tejada-Tayabas, Luz María; Monárrez-Espino, Joel
ABSTEACT: Despite the reported poor dietary habits and risk of weight gain in college students, they remain understudied in Mexico. Mexican college students are in a rapidly changing economic environment; a shift from a traditional, homemade cuisine to a diet more heavily influenced by an industrialized culture seems to be occurring, potentially affecting the quality of their dietary intake. A health and nutrition survey was conducted among 450 Mexican college students to study the relationship between sociodemographic factors and diet quality. Dietary data were used to build macro- and micronutrient scores, dichotomized as low and normal quality. Adjusted odds (OR [95% CI]) were computed to determine the probability of low dietary quality. Breakfast skipping (5.3 [1.2, 22.7]) and risk of anxiety (2.3 [1.3, 4.4]) were associated with a greater risk of low macronutrient quality, and caloric intake < 1, 800 kcal (5.8 [3.5, 9.7]), breakfast skipping (3.7 [1.4, 10.3]), vigorous exercise ≤ 1 h/wk (2.6 [1.3, 5.2]), and soda consumption > 250 mL/d (2.0 [1.2, 3.3]) with low micronutrient quality.